2016
DOI: 10.1186/s40981-016-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

A case of unexpectedly difficult intubation caused by a large asymptomatic choanal polyp

Abstract: We report a case of unexpectedly difficult intubation in a patient with a huge but asymptomatic choanal polyp. A 77-year-old man with invasive bladder cancer was scheduled for total cystectomy under general anesthesia. However, tracheal intubation with a Macintosh laryngoscope proved impossible due to obstruction by a large oropharyngeal tumor. Using a video laryngoscope, intubation was successfully achieved. Choanal polyps are not uncommon, but large choanal polyps reaching the oropharynx appear relatively ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The polyp was arising from the posterior ethmoid sinus and was later removed by endoscopic polypectomy. 6 In our patients, intubation could be performed with minimal difficulty.…”
Section: Discussionmentioning
confidence: 69%
“…The polyp was arising from the posterior ethmoid sinus and was later removed by endoscopic polypectomy. 6 In our patients, intubation could be performed with minimal difficulty.…”
Section: Discussionmentioning
confidence: 69%
“…Clinical manifestations in patients with sphenochoanal polyps are unilateral nasal obstruction and chronic purulent discharge, with headache complaints, especially in the retro-orbital and vertex [1] , [11] . An intranasal polypoid mass may be obtained in anterior rhinoscopy examination, extending from the choanal to the nasopharynx [2] , [12] . Radiological examination is necessary to make the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing the literature, several cases of the giant antrochoanal polyps were reported at different ages [11][12][13][14][15][16][17][18][19]. Besides, Spadijer-Mirkovi et al [20] reported two patients with giant antrochoanal polyps, one of them was a 15-year-old boy and the other was a 38-year-old male.…”
Section: Discussionmentioning
confidence: 99%